Perceptions and reactions to conversational privacy initiated by a conversational user interface. (January 2022) - Brüggemeier, Birgit; Lalone, Philip
Abstract: In 2019, media reports raised awareness about privacy and security violations in Conversational User Interfaces (CUI) like Alexa, Siri and Google. Users report that they perceive CUI as creepy and that they are concerned about their privacy. The European General Data Protection Regulation (GDPR) and several other laws across the globe, give users the right to control processing of their data, for example by requesting deletion of their data and it gives them the right to obtain information about their data. Furthermore, GDPR and other laws advise for seamless communication of user rights, which, currently, is poorly implemented in CUI. We used a bespoke data collection interface to generate speaking chatbots and made them available as tasks on the crowd sourcing platform Mechanical Turk. With those chatbots we simulated how privacy can be communicated in a dialogue between user and machine. We find that conversational privacy can affect user perceptions of privacy and security positively. Moreover, user choices suggest that users are interested in obtaining information on their privacy and security in dialogue form. We discuss implications and limitations of this research. Highlights: Some privacy messages significantly improve privacy and security perceptions. Users tend to accept privacy prompts. Privacy prompts may affect users differently depending on the use case.